Aspects of nerve conduction. - Sabah, N.H.
Myelinated axons have been developed as a solution to the problem of increasing the velocity of conduction of the action potential (AP) along the axon while keeping the axon diameter small. In the best engineering tradition, the solution is simple, elegant, and highly effective. The article explores this and other aspects of nerve conduction that are of interest from an engineering standpoint.
Keywords: Action potential conduction velocity increase; Myelinated axons; Nerve conduction; Simple elegant highly effective solution